Determination of the Shape and Dimensions of the Sensitive Volume for Solid State Detectors Using Monte Carlo Computer Technique - B. Kadhim, Alaa; D. Mahdi, Shams (Iraqi Journal of Science, 2023)
In this research the active volume for a number of solid-state detectors of the type of high-purity germanium (HPGe) crystal was evaluated with different radii and depths using scanning method for diagonal (front) and lateral (side). It has been used for this purpose Monte-Carlo efficiency program after its development by adding a subroutine-program for its (subroutine scanning).Also a program has been written to calculate the stopping power and range for incident charged particle on the detector, in order to determine the exact sufficient energy to stop it inside the detector material. The calculations of our results of efficiency were compared with the results of published efficiency and the comparison is very good in terms of improving the values for practical from the calculated results in other ways.